2019
DOI: 10.21595/vp.2019.21123
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of shear thickening fluid in nanosilica dispersion

Abstract: In this paper, a numerical model of the shear thickening fluid (STF) is generated and the rheological properties are compared with the experimental data. Power Law model has been used to fit the rheological data for STF. Experimental data is taken from a performed study and a user defined function (UDF) has been written to develop the shear thickening behavior. The purpose of this study is to exactly model the behavior of shear thickening fluids by using UDF, to explain the shear-thickening mechanisms under di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…It was shown there that, strictly speaking, the self-similar formulation of the problem of flow and heat transfer is valid and leads to accurate calculation results only at small conicity angles up to 4°. At large conicity angles, separate boundary layers inevitably appear on both surfaces [which is also confirmed by the results of Chauhan et al (2019)], so the self-similar formulation can only be HFF 33,11 used rather for a qualitative assessment of transport processes. For small conicity angles up to 4°, it is enough to use the self-similar heat transfer equation without the inclusion of radial heat conduction because with its inclusion, the Nusselt numbers change by a maximum of 1.5%.…”
Section: Introductionmentioning
confidence: 73%
“…It was shown there that, strictly speaking, the self-similar formulation of the problem of flow and heat transfer is valid and leads to accurate calculation results only at small conicity angles up to 4°. At large conicity angles, separate boundary layers inevitably appear on both surfaces [which is also confirmed by the results of Chauhan et al (2019)], so the self-similar formulation can only be HFF 33,11 used rather for a qualitative assessment of transport processes. For small conicity angles up to 4°, it is enough to use the self-similar heat transfer equation without the inclusion of radial heat conduction because with its inclusion, the Nusselt numbers change by a maximum of 1.5%.…”
Section: Introductionmentioning
confidence: 73%
“…As the conicity angle γ increases above 4°, the flow in the conical gap loses the properties of Couette flows, whereas separate boundary layers appear on the disk and cone. In experiments (Chauhan et al , 2019), it was found that at a relatively large gap height, a pattern is observed that differs from the Couette flow. At the minimum local radii at which the measurements were made, the profile of the tangential velocity in the gap is still linear.…”
Section: Mathematical Model Of Fluid Flowmentioning
confidence: 99%
“…Validation of these theoretical solutions and their comparison with experiments have not been performed, so the practical application of the results of these studies is questionable. Chauhan et al (2019) performed experiments on the flow of a nonNewtonian fluid in a cone-and-disk device supplemented by numerical simulations. In this geometry, the cone did not touch the surface of the disk with its apex, which provided an additional overall height of the gap with a conicity angle of about 6°.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations